Nematicidal Activity of Turmeric Extract against Nematodes Meloidogyne spp. - Ulfa, Maria; Himawan, Toto; Tarno, Hagus (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2021)
In an effort to reduce the impact of synthetic nematicides, a new formula was developed using plant-based nematicides that are more environmentally friendly, one of the basic ingredients that can be used is turmeric. The purpose of this study was to determine the effectiveness of turmeric extract (Curcuma domestica) with various different solvents namely aquades, methanol, and n-hexane at concentration of 5%, 10%, 15% and 20% respectively in inhibiting the activity of Meloidogyne spp. The experiment used was a Completely Randomized Design (CRD). Each treatment was repeated 4 times with 4 controls so that there were 52 experimental units. The result of different research data was analyzed using Analysis of Variance (ANOVA) which was then further tested with Honest Significant Difference (HSD) at the 5% level if real, and t-test for in vivo test. Based on the tested extract, it was found that turmeric extract with various solvent (aquades, methanol, and n-hexane) was effective in inhibiting the activity of Meloidogyne spp. nematodes outside the roots (hatching eggs and penetration), turmeric extract didn’t affect the activity of Meloidogyne spp. in the roots (development and reproduction), vegetable nematicides which the most active in suppressing the population and inhibiting the activity of nematodes was turmeric extract using methanol as a solvent at a concentration of 20%.